Study of Reliability for Main Components and Devices of Die-Cutting Presses for Packaging - N. S. Kohnenko; I. I. Karpunin; V. V. Kuz'mich (Наука и техника)
A large variety of machine operating conditions leads to a difference in the wear rate even for their units being of the same type. Operational time terms of single-type units and machines are not the same, and therefore, numerical expressions of operational reliability will be probabilistic values. Incomplete restoration of original properties of a unit, a negligent repair, a poor maintenance usually lead to the fact that any of several parts independently one from another can determine reliability  of  a  machine  (a unit).  This is especially important  to  consider  when  manufacturing packaging in order to avoid rejects. The operational reliability of modern machines consisting of hundreds, and sometimes thousands of parts, wear processes of which are in a complex relationship,  depends on a number of factors. A study on reliability of main components and equipment devices is an urgent task. Successful operation of printing equipment is possible only if there is a clear organization of preventive work, ensuring preparation of printing machines for printing and post-printing processing. High-performance equipment, such as die-cutting presses, should be regularly inspected, adjusted and maintained in such a way as to obtain standard results at the output. The paper has studied reliability of main components and devices of die-cutting presses based on calculation of failure probability. Calculations have been carried out by analogy with the calculation of the probability of events in the fault tree. Failure diagrams of devices and units of die-cutting presses have been built in the paper. Based on the analysis of the failure probability for main components and devices, graphs of residual life for equipment operation on its life cycle have been constructed in the paper.